Quality of life, attitude towards school and education, and life aspiration of children underthe pantawid Pamilyang Pilipino Program (4Ps). - Garachico, J. Erwin Somblingo
This is a descriptive study aimed to determine the quality of life, attitude towards school and education, and life aspirations of children under the Pantawid Pamilyang Pilipino Program. Sixty-six (66) children from households registered to 4Ps of Baranggays Mat-y and Baybay Norte of the Municipality of Miagao, Iloilo were sampled. The study utilized awareness towards 4Ps open-ended questionnaire, KIDSSCREEN-27 instrument, school attitude questionnaire, attitude towards schooling and educational questionnaire, and the life aspiration index. Results showed that children were aware to be beneficiaries of the program and acknowledge its positive effects on them; however, they do not have any knowledge regarding its nature and purpose. Their level of quality of live was above average and attitude towards school and education was positive. Children under 4Ps value intrinsic aspirations over extrinsic life aspirations. Their goals are to finish school in order to have secure paying occupations, which will enable them to help their families and other people. A key observation in this study was the children?s view towards school and education. They see education as a means of improving their lives; thus, they need to strive hard in school in order to attain their goals in life. The Pantawid Pamilyang Pilipino Program proves beneficial to the respondents since it assists their schooling.